Financial Development in Latin America : Big Emerging Issues, Limited Policy Answers - de la Torre, Augusto (World Bank, Washington, DC, 2012)
This paper argues that the dominant policy paradigm on financial development is increasingly insufficient to address big emerging issues that are particularly relevant for financial systems in Latin America. This paradigm was shaped over the past decades by a fundamental shift in thinking toward market-based financial development and a complex process of financial crises interpretation. The result has been a richly textured policy paradigm focused on promoting financial stability and the convergence to international standards. It argues, however, that there is a growing dissonance between the current paradigm and the emerging issues, which is illustrated by discussing challenges in three areas: stock markets, small and medium enterprise loans, and defined-contribution pension funds. The paper concludes that the dominant policy paradigm is ill-suited to provide significant guidance in relation to the big emerging issues. It emphasizes the need to take a fresh look at the evidence, improve the diagnoses, revisit expectations, and revise the paradigm.